(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Chetan Bhagat has shown his characters with their own intellect and abilities, they are seen to be working shoulder to shoulder with men. As one notice in One Night the Call Center, the number of men and women working in call centers is equal and women choosing to work in night shifts are common. They earn their own living and make career choices. For instance, Esha, in the same novel, exists in Delhi leaving her home in order to make her modeling dream come true. Thus, in this new era, all men and women are equal. Even in case of marriages, now girls declare their own opinions and choices. In the former era, a marriageable boy-girl was bound to marry the match of their parents’ choice and that was regarded as their spiritual duty to repay the debt of parenthood. The best reference will be Priyanka, again in this novel, who makes her own choice in case of marriage quite contrary to her parents’ expectations. Also Ananya in 2 States tries to convince her parents till the end in order to wed her lover Krish.